2003
DOI: 10.1364/ol.28.000301
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-induced two-photon polymerization of inorganic–organic hybrid materials for applications in photonics

Abstract: Investigations of two-photon polymerization of inorganic-organic hybrid materials initiated by femtosecond Ti:sapphire laser pulses are performed. First applications of this technique for the fabrication of three-dimensional microstructures and photonic crystals in inorganic-organic hybrid polymers with a structure size down to 200 nm and a periodicity of 450 nm are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
380
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 570 publications
(397 citation statements)
references
References 14 publications
11
380
1
5
Order By: Relevance
“…MPP was first developed by Strickler and Webb, [62] and has now been used to create a range of high-resolution 3D free-form structures, including microchannels, [63][64][65] cantilevers, [66][67][68] microgears, [69,70] sub-micrometer oscillators, [71] hydrophobic atomic force microscopy tips, [72] and PhCs. [59,67,[73][74][75][76][77][78][79][80][81] Briefly, MPP utilizes the nonlinear nature of the multiphoton excitation process to only excite dye molecules in a very small volume around the focal point, with dimensions on the order of the resolution limit. These excited dye molecules locally initiate a polymerization.…”
Section: Direct Writingmentioning
confidence: 99%
“…MPP was first developed by Strickler and Webb, [62] and has now been used to create a range of high-resolution 3D free-form structures, including microchannels, [63][64][65] cantilevers, [66][67][68] microgears, [69,70] sub-micrometer oscillators, [71] hydrophobic atomic force microscopy tips, [72] and PhCs. [59,67,[73][74][75][76][77][78][79][80][81] Briefly, MPP utilizes the nonlinear nature of the multiphoton excitation process to only excite dye molecules in a very small volume around the focal point, with dimensions on the order of the resolution limit. These excited dye molecules locally initiate a polymerization.…”
Section: Direct Writingmentioning
confidence: 99%
“…However, to the best of the knowledge, the study reported here is the first demonstration of micropillar arrays fabricated by the direct photopatterning of a photocurable hybrid sol-gel thin film. In light of advances made in the synthesis of non-shrinking photocurable hybrid sol-gel materials (Ovsianikov et al 2008) and associated microfabrication techniques (Serbin et al 2003;Ovsianikov et al 2007), it is expected that photocurable hybrid sol-gel materials will receive renewed attention for the fabrication of a range of micropillar-based optical and/or microfluidic platforms including platforms for liquid chromatography (De Malsche et al 2007). …”
Section: Characterisation Of Sol-gel Microfabricated Structuresmentioning
confidence: 99%
“…In this report, the lateral spatial resolution was as high as approximately 100 nm, which is below the diffraction limit. After their works, various three-dimensional micro-sculptures such as Venus statues (Serbin et al, 2003), an opera house (Straub, 2004), jars (Park et al, 2005), and gears (Sun et al, 2004) have been demonstrated using this nonlinear lithographic technique. Functional devices such as full three-dimensional photonic crystals (Deubel et al, 2004), plasmonic elements (Reinhardt et al, 2006) and optically-driven microsystems (Maruo et al, 2003) were also reported.…”
Section: Femtosecond Laser Nonlinear Lithographymentioning
confidence: 99%